Morphological and pathogenic variability in rapeseed and mustard isolates of Scierotinia scierotiorum - ASHA SHIVPURI, R.P. GHASOLlA* and (Indian Phytopathology, 2007)
Studies were conducted to compare the morphological and pathogenic variability among 38 isolates of Sclerotinia sclerotiorum, derived from single lesion/sclerotium on rapeseed and mustard, collected from different locations of 14 districts of Rajasthan. All the isolates showed variation in their morphological traits i.e., colony colour, shape, and sclerotial number, size, position and pattern when grown on PDA. According similarities, 9 groups (G1 to Gj of 38 isolates were established. All the groups were virulent on all the 10 genotypes tested for virulence, except G2 on GM-1 and Gg on RN-393,Rohini and SEJ-2. Among these groups, G6 was the most virulent causing maximum disease incidence (82.44%) followed by G1(77.50 %) and Ga (75.01 %) while Gg had minimum disease incidence (11.08 %). Based on the degree of aggressiveness, present nine groups were divided in two pathotypes i.e., Pathotype-I (G2 , Gs and Gg groups, as these caused less than 18 % disease incidence) and Pathotype-II (having G1 , G3 , G4 , G6 , G7 and Ga groups that caused more than 66 % incidence).